Pselaphinae of the Cameroon Volcanic Line. Part 2. Afroplectus cliveturneri, new name for Afroplectus turneri Hlaváč & Baňař, 2022 (Coleoptera, Staphylinidae) from the island São Tomé - Peter Hlaváč; Baňař, Petr (Zootaxa, 2023)
N/A